Recent Advances in Black-Phosphorus-Based Photonics and Optoelectronics Devices - Debnath, Pulak Chandra; Park, Kichul; Song, Yong-Won (WILEY-V C H VERLAG GMBH, 2018)
In the recent past, 2D black phosphorus (BP) has been intensively studied and examined due to its unique electronic, photonic, and mechanical properties. The tunable and moderate direct bandgap and the high carrier mobility of BP provide enormous potential in electronic and optoelectronic applications. In addition, the unique intrinsic anisotropic characteristics resulting from the puckered structure yield remarkable optical, electronic, transport, mechanical, and thermal characteristics that can be utilized for designing new devices. Significant efforts have been directed toward the synthesis, basic understanding, and applications of BP in the fields of nanoelectronics, ultrafast optics, nanophotonics, and optoelectronics. Here, the current development of electronic, photonic, optoelectronic, and optical devices based on BP is summarized, along with the recent advances in investigating its electronic, optical, and mechanical properties, which form the foundation for next-generation chip-scale integrated devices. In addition, a comprehensive discussion on the requirements for forthcoming studies to upgrade well-systemized fabrication techniques toward large-area, high-yield, and perfectly shielded BP-film production for the development of reliable devices in optoelectronic applications and other areas is provided. Finally, some existing challenges in implementing BP-based optoelectronic and photonic devices are addressed and the prospects for future BP-related research are discussed.
Keywords: FIELD-EFFECT TRANSISTORS; LOCKED FIBER LASER; SATURABLE ABSORBER; OPTICAL-PROPERTIES; EVANESCENT FIELD; PULSE GENERATION; WORK FUNCTION; QUANTUM DOTS; BAND-GAP; GRAPHENE